The Effectiveness of the Role of Social Media in Premarital Education for Generation Z in Purwakarta Regency, Indonesia - Tarigan, Anita Sari (Arkus, 2024)
Social media has become a popular means of communication among generation Z. This gives social media the potential to be used in premarital education. This research aims to analyze the effectiveness of the role of social media in premarital education for generation Z in Purwakarta Regency, Indonesia. This research uses a survey method with a sample of 200 respondents taken randomly from university students in Purwakarta Regency. Data was collected using a questionnaire that measures the effectiveness of the role of social media in premarital education. The research results show that social media is effective in premarital education for generation Z in Purwakarta Regency. This is demonstrated by the results of the analysis, which show that social media has a significant influence on respondents' knowledge, attitudes, and behavior regarding marriage. Based on the results of this research, social media can be an effective means of providing premarital education to generation Z. However, it should be noted that premarital education content on social media must be of high quality and in accordance with the needs of generation Z.